Special Issue on Recent Advances in Machine Learning and Computational Intelligence - Yue Wu; Xinglong Zhang; Pengfei Jia (Applied Sciences, 2023)
Machine learning and computational intelligence are currently high-profile research areas attracting the attention of many researchers [...]